A Selective Harmonic Current Detection Algorithm Based on Quadrature Theory - LI Yu; LANG Fengjie; MA Zhe; WANG Xutao (Kongzhi Yu Xinxi Jishu)
Aiming at the harmonics current detection methods of power grid, a simple effective harmonics current detection algorithm was introduced based on quadrature theory,and its realization and optimization methods were given. With the advantages of low consumption and fast response of the computing resource and storage resource, this algorithm is suit for detecting harmonics current of power quality analysis of electric system. The practical compensation of APF with this algorithm was proposed,which proved its application value.